Preliminary Results of the Survey on Persons with Disabilities Conducted in Selected Metro Manila Cities - Josef T. Yap; Jose Ramon G. Albert; Aubrey D. Tabuga; Celia M. Reyes (Philippine Institute for Development Studies (PIDS), 2009)
The Millennium Development Goals (MDGs) recognize the need to understand the link between disability and poverty. In fact this has become one of the key issues in the subject of poverty reduction in Asia and the Pacific. The United Nations Economic and Social Commission for Asia and the Pacific (UN-ESCAP) noted that persons with disability (PWD) often belong to the poorest segments of the population. To better understand the economic condition of PWDs, it is crucial that information about their economic activities and daily life is obtained. This information can serve as basis for the formulation of policies and intervention strategies for the government, other stakeholders, and the international community. In 2008, the Philippine Institute for Development Studies collaborated with the Institute of Developing Economies (IDE) in Japan, a semigovernmental research institute working for international cooperation between developing countries and Japan, to undertake a survey on PWDs in Metro Manila. The survey covered four Metro Manila cities, namely: Makati, Pasay, Valenzuela, and Quezon City. It was conducted in partnership with the Social Welfare Office of each of the cities and various PWD organizations. This report presents the results of this survey.
Keywords: 330; poverty; household survey; persons with disability (PWDs); Behinderte; Armut; Soziale Lage; Manila; Philippinen